A survey of non-starter lactic acid bacteria in traditional cheeses: Culture dependent identification and survival to simulated gastrointestinal transit. (April 2015) - Ricciardi, Annamaria; Guidone, Angela; Ianniello, Rocco Gerardo; Cioffi, Silvia; Aponte, Maria; Pavlidis, Dimitrios; Tsakalidou, Effie; Zotta, Teresa; Parente, Eugenio
Abstract: Cultivable NSLAB in traditional Pasta filata and ewes' milk cheeses were studied by both PCR-DGGE of cells from Rogosa agar and by isolation and molecular identification after a simulated gastric juice (SGJ) treatment of the cheese. Two to six species were retrieved from each sample. The majority of isolates were identified as Lactobacillus paracasei, Lactobacillus fermentum, Lactobacillus rhamnosus, Enterococcus or Pediococcus . Bile tolerance and bile salt hydrolase (BSH) activity were tested on 88 strains: 64% were able to grow with ≥0.15% bile and 40% were BSH positive. The effect of simulated digestion was tested on 15 strains. Inactivation ranged from 0.15 to 2.93 log cycles; most of the lethality was associated with pancreatic juice treatment. Although SGJ treatment alone may not provide a correct estimate of tolerance to gastrointestinal transit, it allowed selection of strains with a high tolerance to gastric juice, which may be tested as probiotic candidates.